2013
DOI: 10.1007/s11356-013-2064-4
|View full text |Cite
|
Sign up to set email alerts
|

Standard inocula preparations reduce the bacterial diversity and reliability of regulatory biodegradation tests

Abstract: OECD ready biodegradability tests have been central to understanding the biodegradation of chemicals from a regulatory perspective for many decades. They are not fit for contemporary prioritisation of chemicals based on persistence, however, due to the low concentration of inocula used, short duration and high variability between tests. Two OECD standard inoculum pretreatment methods (settlement and filtration) were investigated to observe their effect on the probability of biodegradation and associated change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 37 publications
1
60
1
Order By: Relevance
“…microbial biomass) density is an important factor affecting the outcome of chemical biodegradation tests (Thouand et al 1995;Godhead et al 2014) and in particular, inconsistent 70 test results may reflect differences in inoculum quality because of temporal and spatial variability of microbial community density and diversity within environmental compartments (Courtes et al 1995;Mezzanotte et al 2005).…”
Section: Organisation For Economic Cooperation and Development (Oecd)mentioning
confidence: 99%
See 1 more Smart Citation
“…microbial biomass) density is an important factor affecting the outcome of chemical biodegradation tests (Thouand et al 1995;Godhead et al 2014) and in particular, inconsistent 70 test results may reflect differences in inoculum quality because of temporal and spatial variability of microbial community density and diversity within environmental compartments (Courtes et al 1995;Mezzanotte et al 2005).…”
Section: Organisation For Economic Cooperation and Development (Oecd)mentioning
confidence: 99%
“…For these reasons, use of biofilms in biodegradation tests could provide a means of reducing the chance of common test failures described by Thouand et al (1995) and Godhead et al (2014), by eliminating the 110 'biodegradation lottery' associated with low biomass in regulatory tests (Kowalczyk et al, 2014). However, to date, investigations of the potential to use biofilm inoculum in regulatory tests has centered on laboratory generated inoculum.…”
mentioning
confidence: 99%
“…The biases of the poor comparability for ready biodegradation resulting from different properties of activated sludge and experimental conditions in different laboratory can be avoided. Many reports had indicated that properties of activated sludge (microbial activities, species of the microbial inoculums, et al) might result in great variation of ready biodegradation (Goodhead et al 2014;Kowalczyk et al 2015;Thouand et al 1995). Our study first obtained a number of experimental data under the same experimental conditions to demonstrate the effects of molecular descriptors on ready biodegradation.…”
Section: Effects Of Molecular Properties On Ready Biodegradationmentioning
confidence: 89%
“…PNP represents a readily biodegradable chemical, so that within first-tier Organisation for Economic Co-operation and Development screening tests, natural microbial populations from a range of habitats are generally able to degrade it within a 28-day period without prior exposure to it. However, there can be considerable variation in PNP biodegradation rates within and between studies, the microbial basis for which remains unclear (6).…”
mentioning
confidence: 99%